Faktor-Faktor yang Mempengaruhi Minat Menjadi Akuntan Pendidik di Kota Padang - Utari, Tasya Mardhika; Yunita, Nayang Helma (Jurnal Eksplorasi Akuntansi, 2024)
This research aims to prove and analyze the influence of financial rewards, work environment and job market considerations on interest in becoming an teaching accountant in Padang City. In this research, three leading universities in the city of Padang were used, namely Padang State University, Andalas University and Padang State Polytechnic. The total sample size used was 337 people selected using the proportional random sampling method. The data analysis method was carried out using multiple regression (OLS) and t-statistical testing. Financial awards have a positive and significant effect on the interest of accounting students in Padang City to become teaching accountants. In the second hypothesis testing stage, it was found that the work environment had a positive and significant effect on the interest of accounting students in Padang City to become teaching accountants. At the testing stage of the third hypothesis, it was found that job market considerations had a positive and significant effect on the interest of accounting students in Padang City to become teaching accountants. The findings obtained at the third hypothesis testing stage show that job market considerations have the greatest influence compared to other variables in influencing the interest of accounting students in Padang City to become teaching accountants.